2017
DOI: 10.1007/s10729-017-9415-5
|View full text |Cite
|
Sign up to set email alerts
|

Population-level intervention and information collection in dynamic healthcare policy

Abstract: We develop a general framework for optimal health policy design in a dynamic setting. We consider a hypothetical medical intervention for a cohort of patients where one parameter varies across cohorts with imperfectly observable linear dynamics. We seek to identify the optimal time to change the current health intervention policy and the optimal time to collect decision-relevant information. We formulate this problem as a discrete-time, infinite-horizon Markov decision process and we establish structural prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 78 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…These 2 features, that c c s (n s ) and ENBS s (n s ) are or are well-approximated to be continuously differentiable, are present in EVSI examples in the literature (e.g., see realproblem examples in figure 9 of McKenna et al, 34 figure 5 of Stevenson et al, 35 figure 4 of Cipriano and Weber, 36 and Kunst et al, 37 where variable cost functions are linear and EVSI is a smooth Gaussian approximation). Therefore, features of the necessary optimality conditions for OPT2 provide important insight into many applied research funding allocation problems.…”
Section: Reformulation Of the Optimization Problem To Gain Insight Inmentioning
confidence: 95%
“…These 2 features, that c c s (n s ) and ENBS s (n s ) are or are well-approximated to be continuously differentiable, are present in EVSI examples in the literature (e.g., see realproblem examples in figure 9 of McKenna et al, 34 figure 5 of Stevenson et al, 35 figure 4 of Cipriano and Weber, 36 and Kunst et al, 37 where variable cost functions are linear and EVSI is a smooth Gaussian approximation). Therefore, features of the necessary optimality conditions for OPT2 provide important insight into many applied research funding allocation problems.…”
Section: Reformulation Of the Optimization Problem To Gain Insight Inmentioning
confidence: 95%
“…At each time, the policy maker can choose to screen the current cohort of 50-year olds and to purchase sample information about parameters influencing the decision. Using a stochastic dynamic programming approach, we have previously shown that it may be optimal to delay information collection about the time-varying parameter (HCV prevalence) until the information is more likely to result in a change in policy [26].…”
Section: Introductionmentioning
confidence: 99%
“…Optimal information acquisition at time t = 1.Remark 2 (Information-Cost Threshold). The expression for κ * 1 implies the cost thresholdβ d (1 + α)σ6 d /4, so that nontrivial market intelligence is economical if and only if the firm's information-acquisition cost is such that β ∈ (0,β d ).…”
mentioning
confidence: 99%
“…Some applications in healthcare are of this form; see, e.g., Cipriano and Weber[6] who determine the amount of information to collect (using public health screening) to inform a planner's decision to discontinue a public health screening program for hepatitis C.…”
mentioning
confidence: 99%
See 1 more Smart Citation